2015
DOI: 10.5392/jkca.2015.15.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Secondary Traumatic Stress among Public Social Welfare Specialists

Abstract: This study was to identify major risk factors associated with secondary traumatic stress in a sample of 654 public social welfare specialists. Findings indicated that 69.0% of the subjects experienced secondary traumatic stress, and 36.9% of them were in a high-risk group. Multiple regression analysis showed that the risk of the secondary traumatic stress was associated with gender, work hours, physical violence and threats from clients, coping strategies, and vocational self-efficacy. Based on these results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Among the subfactors of occupational stress, physical environment and job instability were found to significantly affect secondary traumatic stress. In a previous study, Yang and Kim [33] reported that the risk of experiencing violence was the highest among the factors affecting secondary traumatic stress in female social workers. According to Bride [34], secondary traumatic stress was higher when there was higher probability of accidents or assault and verbal abuse from service recipients, greater physical burden and long hours of work in an uncomfortable posture.…”
Section: Discussionmentioning
confidence: 96%
“…Among the subfactors of occupational stress, physical environment and job instability were found to significantly affect secondary traumatic stress. In a previous study, Yang and Kim [33] reported that the risk of experiencing violence was the highest among the factors affecting secondary traumatic stress in female social workers. According to Bride [34], secondary traumatic stress was higher when there was higher probability of accidents or assault and verbal abuse from service recipients, greater physical burden and long hours of work in an uncomfortable posture.…”
Section: Discussionmentioning
confidence: 96%
“…Although our participants reported that maintaining boundaries could be challenging, setting boundaries that separate professional work and personal life served to protect them from feeling overwhelmed or helpless. Indeed, in a study by Yang and Kim (2015), the use of avoidance coping strategies among public social workers was associated with decreased levels of secondary trauma. These avoidance or boundary-setting strategies were also reported in previous studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the experiences of cancer care workers focused on oncology nurses and physicians (Hesselgrave, 2014; Najjar et al., 2009; Slocum-Gori et al., 2013), but inadequate attention has been paid to oncology social workers’ compassion fatigue and how they cope with such fatigue. Recently, several studies on social workers’ secondary traumatic stress have been conducted among South Korean samples (Um and Jang, 2014; Yang and Kim, 2015), and interventions for secondary traumatic stress have been explored (Choi, 2008). Yang and Kim (2015) examined risk factors for secondary traumatic stress among female public social workers, and Um and Jang (2014) investigated the process of coping with secondary traumatic stress of child welfare social workers.…”
mentioning
confidence: 99%
See 1 more Smart Citation